Revision of South African chiggers (Acariformes: Trombiculidae) originated from the collection of R.F. Lawrence, with redescriptions of nine species - Stekolnikov, Alexandr A. (Zootaxa, 2024)
A revision of the chigger mite collection in the KwaZulu-Natal Museum (NM, Pietermaritzburg, South Africa) resulted in finding holotypes or paratypes for 15 of the 51 species described by R.F. Lawrence in 1948–1951 and originally deposited in this museum. Five species of chigger mites incompletely described by him have been redescribed based on the type series and additional specimens from the collections of NM and the Natural History Museum (London, UK): Herpetacarus (Abonnencia) alticolus (Lawrence, 1951), Schoengastia scincicola Lawrence, 1949, S. monticola Lawrence, 1949, S. mabuyana Lawrence, 1949, and Neotrombicula (Anamasticula) rhodesiana (Lawrence, 1949). Schoengastia gerrhosauri Lawrence, 1949 was redescribed partly. One new synonym has been established: Herpetacarus (Abonnencia) longispinus (Radford, 1948) (= Ascoschoengastia rhabdomyia Lawrence, 1951, syn. nov.); this species has been redescribed based on the types of H. longispinus and non-type specimens of A. rhabdomyia. Riedlinia (Trombigastia) cadei (Vercammen-Grandjean and Brennan, 1957) has been for the first time recorded in South Africa. Microtrombicula (Microtrombicula) zumpti Vercammen-Grandjean, 1965, previously known only from its probably lost holotype, and Schoengastia pseudocordyli Lawrence, 1949 have been redescribed based on new specimens found among unidentified materials deposited in the NM collection.